Construction of Infectious Clones of Begomoviruses: Strategies, Techniques and Applications - Mohd Faiz Mat Saad; Aziz Ramlee Sau; Muhamad Afiq Akbar; Syarul Nataqain Baharum; Ahmad Bazli Ramzi; Noraini Talip; Hamidun Bunawan (Biology, 2021)
Begomovirus has become a potential threat to the agriculture sector. It causes significant losses to several economically important crops. Given this considerable loss, the development of tools to study viral genomes and function is needed. Infectious clones approaches and applications have allowed the direct exploitation of virus genomes. Infectious clones of DNA viruses are the critical instrument for functional characterization of the notable and newly discovered virus. Understanding of structure and composition of viruses has contributed to the evolution of molecular plant pathology. Therefore, this review provides extensive guidelines on the strategy to construct infectious clones of Begomovirus. Also, this technique’s impacts and benefits in controlling and understanding the Begomovirus infection will be discussed.